Asthma and Chronic Obstructive Pulmonary Disease Associated With Occupational Exposure in Dairy Farmers - Importance of Job Exposure Matrices - Stoleski, Sasho; Minov, Jordan; Karadzinska-Bislimovska, Jovanka; Mijakoski, Dragan; Atanasovska, Aneta; Bislimovska, Dragana (ID Design Press/Scientific Foundation SPIROSKI, 2019)
To evaluate the prevalence of chronic respiratory symptoms, lung function impairment, and chronic obstructive respiratory diseases in dairy farmers. Our objective is to then examine their relation to exposure duration and to explore the usefulness of job exposure matrices as tools for exposure assessment, and predictors for respiratory health impairment.
Keywords: Respiratory symptoms; Spirometry; Farming; Questionnaire; Job exposure; Chronic obstructive lung diseases